Keragaan Permesinan dan Keteguhan Rekat Kayu Jati Cepat Tumbuh Terdensifikasi - Herianto Siahaan; Imam Wahyudi (Institut Pertanian Bogor, 2021)
The objective of this study was to analyze machining performance (characteristic and quality), as well as bonding quality of densified wood, and then compared to those of un-treated (control) wood and boron-treated wood. Characteristic and quality of machining properties were directly evaluated by qualified technician during processing, while bonding quality was evaluated through its shear strength. The results showed that densification employed was able to improve machining performance and bonding quality of the 5-year-old faster-grown teakwood. Compared to control wood and boron-treated wood, machining performances of densified teakwood are greater, while bonding quality increased by 18.79 and 26.86%, respectively. The surface became much fine and even, and has similar colour to older teakwood. Analysis hierarchy process (AHP) proves that densified teakwood is the best raw material for furniture manufacturing since its machining performances, appearance, colour, and bonding quality are better either than control wood or boron-treated wood. Keywords: AHP, bonding quality, densification, faster-grown teakwood, machining performance